2018
DOI: 10.1016/j.dadm.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Memory concerns in the early Alzheimer's disease prodrome: Regional association with tau deposition

Abstract: Introduction Relationship between self– and informant memory concerns and tau aggregation was assessed in adults at risk for Alzheimer's disease (AD). Methods Regional mean standardized uptake value ratios were extracted from [ 18 F]flortaucipir positron emission tomography (PET) scans of 82 at-risk adults in the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort. Associations between self– and informant ECog memory scores and tau aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
0
18
2
Order By: Relevance
“…The development of selective tau tracers, such as the most extensively used tracer 18 F-Flortaucipir [ 47 ], allows researchers to investigate regional distribution of tau pathology in the living human brain [ 46 , 48 , 49 ]. In the preclinical stage, the relationship between the symptoms of SCD and tau burden has been reported by Swinford and colleagues [ 50 ]. They scanned SCD subjects using 18 F-flortaucipir PET and determined that the self-reported memory concern was associated with frontal tau levels, whereas the informant-reported concern was related to parietal tau levels.…”
Section: Positron Emission Tomographymentioning
confidence: 82%
See 1 more Smart Citation
“…The development of selective tau tracers, such as the most extensively used tracer 18 F-Flortaucipir [ 47 ], allows researchers to investigate regional distribution of tau pathology in the living human brain [ 46 , 48 , 49 ]. In the preclinical stage, the relationship between the symptoms of SCD and tau burden has been reported by Swinford and colleagues [ 50 ]. They scanned SCD subjects using 18 F-flortaucipir PET and determined that the self-reported memory concern was associated with frontal tau levels, whereas the informant-reported concern was related to parietal tau levels.…”
Section: Positron Emission Tomographymentioning
confidence: 82%
“… Snitz et al (2015) [ 24 , 26 ] MFQ CFQ SCCS PiB-PET Cross-sectional Total: n=92(81.2±8.4) MFQ score relate to global PiB retention Timmers et al (2019) [ 38 ] Memory clinic consultation Intact cognition 18 F-florbetapir PET Cross-sectional Total: n=107(64±8) Higher 18 F-florbetapir BP ND relates to steeper rate of decline on memory, attention/executive and language Verfaillie et al (2019) [ 33 ] CCI SCF Composite of 4 questions 18 F-florbetapir PET Cross-sectional Total: n=106(63.83±7.65) Higher cortical amyloid deposition relates to SCD-related worries and higher memory deficit awareness but not to SCD questionnaires Zwan et al (2016) [ 44 ] MAC-Q IQCODE-S PiB-PET 18 F-flutematamol PET Cross-sectional Low amyloid burden: n=229(71.9±6.5) High amyloid burden: n=78(75.0±7.2) SMC with younger age and ApoE ɛ4 carriers had higher amyloid burden. Swinford et al (2018) [ 50 ] E-Cog 18 F-flortaucipir PET Cross-sectional CN: n=40(76.48±7.211) SMC: n=11(71.55±5.11) EMCI: n=31(75.32±7.29) Memory concern and the self-perception relate to tau aggregation. Cavedo et al (2018) [ 60 ] Memory complaints 18 F-flortaucipir -PET FDG-PET MRI Cross-sectional Women: n=201(76.02±3.24) Men: n=117(76.05±3.85) Men had higher amyloid load glucose hypometabolism and lower RSFC.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Identifying risk factors that may influence cognitive decline at its earliest stages is critical as interventions will most likely be more effective during an early prodromal phase before neurodegenerative or cognitive damage is irreversible. 53 Data on the relation between hearing loss and SCF decline are scarce. Our findings are consistent with our previous study among older men that found the risk of subjective cognitive decline was 30% higher among men with self-reported mild hearing loss, and 42-54% higher among men with moderate or TA B L E 6 Prevalence and adjusted odds ratios (95% confidence intervals) for subjective cognitive function according to 2006 hearing status worse hearing loss, 25 and with a smaller study that found self-reported hearing difficulty (queried as "even with a hearing aid") was associated with 22% (95% CI: 14-29%) higher odds of poorer SCF (assessed using 4 questions) 5 years later.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we detected that LMCI participants had higher informant-report ECog scores than the EMCI participants, and both groups showed no difference in the self-reported ECog scores. Swinford (28) had found that self-and informant-ECog memory scores were not correlated with one another in the amyloid-positive adults, and suggested that the two measurements of the subjective memory complaints may be independent. Drawing on his assumptions about the results in his research, we hypothesized that the participants in prodromal AD group might be involved with the more outward signs of cognitive decline that could be noticed by an observer who knew the individual well.…”
Section: Discussionmentioning
confidence: 99%